2005
DOI: 10.1002/ccd.20443
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter atrial septal defect closure: Modified balloon sizing technique to avoid overstretching the defect and oversizing the Amplatzer septal occluder

Abstract: The objective of this study was to evaluate a new technique of sizing atrial septal defects (ASDs) for transcatheter device closure. ASD closure using the Amplatzer septal occluder (ASO) device is commonly performed. Complications, including arrhythmias, pericardial effusions, and perforations, may be related to oversizing ASDs and choosing larger devices. Two methods were used to size ASDs using a compliant balloon. In some patients, the balloon was inflated until a waist was visible [(+)waist]; in others, on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 18 publications
2
50
0
Order By: Relevance
“…25 Some studies suggest that balloon calibration techniques oversize the defect. 9 Modified BS techniques have been developed to avoid overstretching. 9,25 In this study, a modified BS technique using the pull-through technique was also applied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…25 Some studies suggest that balloon calibration techniques oversize the defect. 9 Modified BS techniques have been developed to avoid overstretching. 9,25 In this study, a modified BS technique using the pull-through technique was also applied.…”
Section: Discussionmentioning
confidence: 99%
“…9 Modified BS techniques have been developed to avoid overstretching. 9,25 In this study, a modified BS technique using the pull-through technique was also applied. Despite this technique being believed to decrease overstretching of the rims, an overestimation of the ASD diameters by BS compared with 3D-TEE, particularly in round ASDs was found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,12,14,15) This is because most ASD have pliable and redundant rim tissues. Although some authors have suggested that the balloon stretched size overestimates the real size, 16) balloon stretch size is still A B being adopted as a gold standard until a new consensus is reached in the future. In this study, we found that the balloon stretched size may be 22 to 34% larger than the size measured by echocardiography.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid oversizing with respect to avoiding erosion, the stop-flow method was used for measurement in every patient. 13 Deployment of the device was performed by an approach from either the left upper pulmonary vein or right pulmonary vein. A Hausdorff sheath was used in 14 cases of relatively large defects compared with body size.…”
Section: Sizing Balloon and Implantation Techniquementioning
confidence: 99%